اتجاهات الاكاديميين الليبيين نحو البرامج السياسية بالقنوات الفضائية الليبية في ظل الأزمات السياسية - العود أ.عادل أحنيش (المجلة الدولية لعلوم الإعلام والاتصال, 2024)
ملخص الدراسة: تناولت الدراسة موضوع اتجاهات الاكاديميين الليبيين نحو البرامج السياسية بالقنوات الفضائية الليبية في ظل الازمات السياسية دراسة ميدانية أجريت على أساتذة جامعة سرت، واستهدفت هذه الدراسة التعرف على مدى اهتمام القنوات الفضائية بالبرامج الحوارية السياسية من وجهة نظر أساتذة جامعة سرت، وكذلك أهم القنوات الليبية التي تهتم بالبرامج الحوارية السياسية والتعرف على الميزات الإيجابية والاثار السلبية لهذه البرامج على النخبة الاكاديمية، وقد اعتمد الباحثين على العينة العشوائية البسيطة والبالغ عددها 30 مبحوثاً من أعضاء هيئة التدريس بمختلف تخصصاتهم العلمية. هذه الدراسة تطلبت الاعتماد على المنهج الوصفي التحليلي، حيث اظهرت نتائج الدراسة الميدانية بأن الأكاديميين الليبيين أحياناً ما يتابعوا البرامج الحوارية السياسية بالقنوات الفضائية الليبية وبنسبة بلغت (66.7%)، وأيضاً بينت نتائج الدراسة بأن أفراد عينة الدراسة يتابعون البرامج الحوارية السياسية في قناتي "ليبيا 24/ وليبيا الحدث"، وكذلك أكدت نتائج الدراسة بأن نسبة (29.5%) من أفراد عينة الدراسة يرون بأن أهم الازمان السياسة متابعة أزمة الانقسام السياسي. Abstract The study dealt with the subject of Libyan academics’ attitudes towards political programs on Libyan satellite channels in light of the political crises, A field study conducted on professors at the University of Sirte, This study aimed to identify the extent of satellite channels’ interest in political talk shows from the point of view of Sirte University professors, As well as the most important Libyan channels that are interested in political talk shows and identifying the positive features and negative effects of these programs on the academic elite, The researchers relied on a simple random sample of 30 respondents from faculty members in their various scientific specializations. This study required reliance on the descriptive analytical approach, as the results of the field study showed that Libyan academics sometimes follow political talk shows on Libyan satellite channels, at a rate of (66.7%), The results of the study also showed that members of the study sample follow political talk shows on the “Libya 24/ and Libya Al Hadath” channels, The results of the study also confirmed that (29.5%) of the study sample members believe that the most important time in politics is following up on the crisis of political division.